Factors Determining Technical Wear on the Example of the Analysis of the Technical Condition of Balconies in Multi-Family Housing. Issue 2 (February 2019) - Nowotarski, Piotr; Gajzler, Marcin
Abstract: The problem related to the technical wear of the building affecting the state of the structure is crucial from the end user perspective. It influences the maintenance phase in the lifecycle of the object. Researchers agree that knowledge about factors influencing the technical state of the construction is important in terms of cost estimation of works needed for keeping the object in appropriate conditions. The article presents the idea of determining technical wear of the construction, based on the detail analysis of the technical condition of balconies. Authors focus their attention to present possible aspects of technical wear of the building, especially considering external conditions influence on the construction. For this purpose, investigation was performed on the set of 74 balconies located in the block of flats in city of Poznań, Poland, where modernization is planned to be done within the next 12 months. Authors prepared detailed analysis taking into account current technical state of among others: handrails, balustrades, walls, upper plate, bottom plate, floor surface, flanks, plasters etc. From the analysis report was prepared showing what are the most intensive technical factors influencing state of the building and how they affect visual and constructional aspects of balconies. Based on those information, authors came to the conclusions that due to different errors committed on the phase of executing construction works, as well as adverse and aggressive weather conditions, state of the structure can show faster tendencies to destruction, which from the end-user point of view can cause problems and results in the need of costly repairs.